2008
DOI: 10.1007/s10295-008-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of raw feather by a novel high molecular weight extracellular protease from newly isolated Bacillus cereus DCUW

Abstract: Biotreatment of feather wastes and utilization of the degraded products in feed and foodstuffs has been a challenge. In the present study, we have demonstrated the degradation of feather waste by Bacillus cereus DCUW strain isolated during a functional screening based microbial diversity study on East Calcutta Wetland Area. A high molecular weight keratinolytic protease from feather degrading DCUW strain was purified and characterized. Moreover, utilization of degraded products during feather hydrolysis was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 35 publications
0
40
1
3
Order By: Relevance
“…A wide range of variations can be observed in fungal keratinases (18-200 kDa) [36]. Even though the present study was contradictory to the above reports [3,4,34] later major variations are existing even among the fungal keratinases are confirmed with the report [36]. …”
contrasting
confidence: 56%
“…A wide range of variations can be observed in fungal keratinases (18-200 kDa) [36]. Even though the present study was contradictory to the above reports [3,4,34] later major variations are existing even among the fungal keratinases are confirmed with the report [36]. …”
contrasting
confidence: 56%
“…In our previous work on feather-degrading protease (Ghosh et al, 2008), we found 70±10 kDa protein bands during purification studies. Moreover, during the native protein purification, we found that several smaller fragments (both proteolytically active and inactive) were generated from the purified protease.…”
Section: Expression and Characterization Of Deletion Mutantsmentioning
confidence: 76%
“…The present analysis suggests that this C-terminal domain is probably responsible for the substrate binding via protein-protein interactions. Previously we have shown that this protease could degrade feather residues (Ghosh et al, 2008). In the present study, the feather keratin-binding assay was designed to check whether the C-terminal domain specifically binds to feather.…”
Section: Full-length Sequencing Of Vpr Gene and Domain Analysismentioning
confidence: 99%
“…Kecernaan yang rendah disebabkan karena adanya kandungan kolagen pada MBM (Ravindran et al, 2005) dan keratin pada HCFM (Ghosh et al, 2008) …”
Section: Pendahuluanunclassified